Optimisation of Black Soldier Fly (Hermetia Illucens) Production for Organic Waste Management in a Small-scale Institutional Facility - Njagi, Elizabeth Karimi (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Safe management of organic waste is especially challenging in resource-constrained countries. This has led to unregulated faecal waste management posing a great risk to human health and the environment. Owing to this, there has been a focus on non-sewed sanitation such as onsite sanitation technology that uses low-cost systems such as container-based systems (CBS). in urban areas of low- and middle-income countries. However, even with the use of onsite technology using CBS, there is a limited management system in place for the resulting accumulation of faecal waste emptying and transportation costs of faecal waste. Consequently, the lack of potential recyclers for faecal and food waste is also a major concern. One of the solutions to poor management of organic waste is to create value from waste. One way to do this is the use of black soldier larvae (BSFL) bioconversion technology. Utilization is however hindered by limited information on black soldier fly (BSF) rearing strategies, especially at the non-feeding stages of adult emergence and egg oviposition. In this study, we assessed the optimisation of black soldier production at the post-feeding stages of adult emergence and oviposition. Five-day-old larvae were introduced into containers using different feed substrates, and growth was monitored until the post-feeding stage. The feed substrates used were faecal matter, kitchen waste, and a mixture of kitchen waste and faecal matter at a ratio of 1.1. Plastic grooved pipes of different colours were placed in a container with an attractant for BSF to lay eggs whose weight was monitored. Space requirement was determined by placing post-feeding larvae in cages of different dimensions. Performance was measured by the number of adults that emerged and the weight of eggs. Study results showed that the black-coloured ovipositing structure was most preferred for ovipositing while yellow was the least preferred. Cages of 2.5 and 2m performed better in terms of egg production and adult emergence. Co-treatment of faecal matter and kitchen waste resulted in a better substrate for adult emergence and egg production. Our study gives the way for optimised rearing of BSF for faecal matter management from onsite facilities, managing other organic wastes, and providing alternative animal feed and sustainable farming practices.